EFFECT OF DOSE FERTILIZER AND CULTIVARS TO THE ACTIVE COMPOUND GLYCERYL TRIOLEATE OF Coix lacryma-jobi L. - Chung Tien Nghiem; Geng Li Jiang; Ke Fang Shen; Zhan Wang (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2016)
In order to provide a method for quality control of glyceryl trioleate in Coix lacryma-jobi L., this paper focused on differentiating the glyceryl trioleate compound in 14 cultivars and effect of nitrogen on glyceryl trioleate in Coix seed by clustering of High Performance Liquid Chromatography (HPLC). This research was carried out to find a variety that has active glyceryl trioleate with the highest content and to investigate the effect of nitrogen to the active ingredients of glyceryl trioleate in Coix lacryma-jobi L. and its effect in Coix lacryma-jobi L. treatment. The standard regressive curve equation of glyceryl trioleate obtained by using HPLC was: Y = (7.106) X- 495293, R² = 0.9997. The average reproducible experiment result of glyceryl trioleate is 0.097, RSD (relative standard deviation) is 1.95%; recovery rate is 97.69% and RSD is 0.89%. The experiment measured the glyceryl trioleate content of 14 varieties of Coix lacryma-jobi L using Qianyin #1 (C14). The result showed that fertilizer combination N10F2 (4:1:2:3) produced the highest glyceryl trioleate content in Coix lacryma-jobi L. Thus, nitrogen that applied in the fertilizer for 150kg ha-1 and the ratio of pre plant application including seedbed application, tillering application and earing application were optimized at 4:1:2:3 ratio.